Selection Cuttings as a Tool to Control Water Table Level in Boreal Drained Peatland Forests - Leppä, Kersti; Hökkä, Hannu; Laiho, Raija; Launiainen, Samuli; Lehtonen, Aleksi; Mäkipää, Raisa; Peltoniemi, Mikko; Saarinen, Markku; Sarkkola, Sakari; Nieminen, Mika (Frontiers in Earth Science, 2020)
Continuous cover management on peatland forests has gained interest in recent years, in part because the tree biomass with significant evapotranspiration capacity retained in selection cuttings could be used as a tool to optimize the site water table level (WTL) from both tree growth and environmental perspectives. This study reports WTL responses from six field trials established on fertile Norway-spruce-dominated drained peatland forests across Finland. At each site, replicates of different intensity selection cuttings (removing 17–74% of stand basal area) or clear-cut in parallel with intact control stands were established and monitored for WTL for 2–5 post-harvest years. Observed WTL rose after selection cuttings and the response increased with harvest intensity and depended on the reference WTL, i.e. larger responses were found during dry summers or in more southern location. Selection cuttings removing about 50% of stand basal area raised WTL typically by 15–40%. Using a process-based ecohydrological model, tested against data from the field trials, we show that the role of tree stand in controlling WTL clearly decreases along the latitudinal climate gradient in Finland. This suggests that the potential of controlling WTL using selection cuttings is more prominent in southern compared to northern Finland. Predictions with future climate (2070–2099) further indicated a general decrease of WTL and that the importance of the tree stand in controlling WTL will increase especially in northern Finland. The results overall thus suggest that selection cuttings can be used as a tool to control WTL in boreal drained peatland forests, and the potential is likely to increase in future climate.